A Review on Platelet Activating Factor Inhibitors: Could a New Class of Potent Metal-Based Anti-Inflammatory Drugs Induce Anticancer Properties? - Vasiliki D. Papakonstantinou; Nefeli Lagopati; Effie C. Tsilibary; Constantinos A. Demopoulos; Athanassios I. Philippopoulos (Bioinorganic Chemistry and Applications)
In this minireview, we refer to recent results as far as the Platelet Activating Factor (PAF) inhibitors are concerned. At first, results of organic compounds (natural and synthetic ones and specific and nonspecific) as inhibitors of PAF are reported. Emphasis is given on recent results about a new class of the so-called metal-based inhibitors of PAF. A small library of 30 metal complexes has been thus created; their anti-inflammatory activity has been further evaluated owing to their inhibitory effect against PAF in washed rabbit platelets (WRPs). In addition, emphasis has also been placed on the identification of preliminary structure-activity relationships for the different classes of metal-based inhibitors.